Plays in Japanese Occupation Period (1942—1945): Some Notes about Indonesian People in the War Era - Yoesoef, M. (Makara Human Behavior Studies in Asia, 2010)
Many plays in Japanese occupation period (1942—1945) were full of propaganda of Japanese Military Government that tried to influence Indonesian people to assist Japanese troops in fighting American army in World War II. Literature was used as a proper propaganda tool, especially plays, where people could get the message directly about what they should do in war situation. A lot of artists were gathered by the Propaganda Service Office (Sendenbu) to work on their fields of creativity (music, sculpture, literature, drama, painting) in order to encourage Indonesian people to participate in the war. Some playwrights such as Usmar Ismail, El Hakim. Armijn Pane, Soetomo Djauhar Arifin, and Merayu Sukma enthusiastically welcomed the program. They wrote many plays that were played by various drama groups that sprang up in that period.